Dapsone as a potential treatment option for Henoch-Schönlein Purpura (HSP). (October 2017) - Lee, Keum Hwa; Park, Jae Hyon; Kim, Dong Hyun; Hwang, Jimin; Lee, Goeun; Hyun, Jae Seok; Heo, Sung Taik; Choi, Ji Hoon; Kim, Minwoo; Kim, Minhye; Kim, Seong Il; Eisenhut, Michael; et al.
Abstract: Henoch-Schönlein Purpura (HSP, IgA vasculitis) is an immunoglobulin A (IgA) mediated disorder characterized by systemic vasculitis with variable presentation, frequently affecting the skin, mucous membrane, joints, kidneys, and rarely lungs and the central nervous system. Interestingly, enhanced production of interleukin-8 (IL-8) levels are found during active disease and increased levels have been reported in supernatants from human umbilical venous endothelial cells after stimulation with sera from patients affected by HSP. While corticosteroid therapy is currently the recommended treatment for HSP, dapsone, an anti-leprosy agent, has also recently been suggested to have therapeutic efficacy due to its ability to suppress IL-8. Moreover, in addition to IL-8 suppression, dapsone has been reported to exert various anti-inflammatory effects by inhibiting the generation of toxic free radicals, myeloperoxidase mediated halogenation that converts H2 O2 to HOCl, leukocyte chemotaxis, production of tumor necrosis factor, and other anti-inflammatory molecules. This review aims to provide a solid hypothesis for the pathogenesis of vasculitis in HSP. Moreover, we highlight potential mechanistic actions of dapsone in hopes that dapsone may be considered as an alternative viable treatment for patients affected by HSP.